The Effect of Marketing for Indian Frozen Meat in the Local Market and Its Reflection on the Microbial Load - Saleh Al- Timimi, Salim; Mohammed, Sudad Jasim; Fareed Ali, Ibtsam (Iraqi Journal of Science, 2026)
This study aimed to investigate the Microbial Load of Indian Meat available inlocal market of Baghdad city to ensure that they are free from bacteria and toindicate the safety of product depending on the Iraqi standards. in addition to theestimation of some elements such as (Iron, Copper, Lead, Cadmium, Chrome) , wegathered 30 trade brands of meat included: (Khairat Karbala1,Khairat Karbala2,Thamarat Karbala1, Thamarat Karbala2, Alwakeel1, Alwakeel2, Anbar, AnwarKarbala, Alfakher, Alraudhatain, Almurad, Zamzam, Rayat, Karbala, Karbala,Alanna1,SAS,Alahmed,MKR,Altamam,Anwar,Almuntathr,Alwesam,Albayader,Ambar,Thamarat Karbala,Alhalal,Alanwar,Alhana,Alfakher,Alana2).the bacteriologicaltest for these samples which included(total bacteria number, total coliform number,salmonella number, Staphylococcus bacteria number) were done.The result of study shows the increasing in the bacteria total number in(Alanwar ) which reached 410×28 cfc/g while less number was 110×28 cfc/g in(Almurad) brand. Also the highest number for Staphylococcus bacteria was 410×13cfc/g found in (MKR) brand, while four brands (Anbar, Anwar Karbala, Alfakher)content on Salmonella and the others were free from it. As for coliform bacteria itsnumber was between310×1 cfc/g - 310×15 cfc/g . the highest concentration forIron 5.424μg/g in (Alana) brand and less concentration was 0.200μg/g in(Albayader) brand , the concentration of Cooper element was between 1.451μg/g -0.001μg/g , while the highest concentration of Lead element 0.639μg/g in(Alwesam) brand . Both brands (Almurad, Albayader) were free from this element.The highest concentration of Cadmium appears in ( Thamarat Karbala 4, Alana1)reached 1.541μg/g while other brands were free from this element . According toChrome the highest concentration appears in two brand ( Ambar,Alanwar) reached0.045μg/g while less concentration appears in ( zamzam) brand reached 0.003μg/g,other brands free from this element